Measurement techniques in plant science - Hashimoto, Yasushi, 1936- (Academic Press, 1990)
Any explanation of the physiological ecology of plant growth--why plants survive in particular environments--requires the measurement of the effects of environmental factors. This book reviews the history, development, and current status of instruments and measurement techniques that have been particularly useful in field studies of plant physiological ecology. It will be of interest to researchers and students in plant physiology and biochemistry, crop scientists, horticulturalists, and foresters. There is particularly noteworthy coverage of: * Miniaturized, portable gas exchange measurement systems * Permanent field installation for transportationo measurements * Automated plant-water sensing system * Use of chlorophyll fluorescence for screening of tolerant genotypes.